Biotite and muscovite 40Ar/39Ar geochronological constraints on the post-Svecofennian tectonothermal evolution, Forsmark site, central Sweden - Söderlund, Pia; Hermansson, Tobias; Page, Laurence; Stephens, Michael (International Journal of Earth Sciences, 2009)
In order to characterize the post-Svecofennian tectonothermal evolution of the Fennoscandian Shield, 40Ar-39Ar biotite and some 40Ar-39Ar muscovite geochronological data are reported from a total of 30 surface outcrop and 1000 m long borehole samples at Forsmark, central Sweden. The thirteen surface samples were collected across three branches of a major WNW to NW trending system of deformation zones, whereas the boreholes were drilled within a tectonic lens, in between two of these zones. The 40Ar-39Ar biotite ages indicate that the present erosion surface, in central Sweden, cooled below 300 °C at 1.73-1.66 Ga, and that the rocks could respond to stress by brittle deformation between 1.8 and 1.7 Ga. The variation in surface ages is suggested to be due to faulting along the large WNW to NW trending deformation zones, following the establishment of a sub-Cambrian peneplain. The minor variation of ages within a single crustal block may be due to disturbance along ENE to NNE trending fracture zones. Possible cooling paths, derived from 40Ar-39Ar hornblende, muscovite and biotite ages, were calculated for the time interval from 1.80 to 1.66 Ga, when the area cooled from 500 °C to 300 °C. Between 1.70 and 1.64 Ga, uplift rates of c. 22 m/m.y. were calculated from borehole 40Ar-39Ar biotite data. Tectonothermal histories, inferred from the combined cooling and uplift rates, are related to simple slow cooling after the Svecofennian orogeny, to crustal movement in response to far-field effects of c. 1.7 Ga orogenic activity further to the west or to a combination of these possibilities.